Treinamento do ator: sobre saberes e práticas de Carlos Simioni - Marcelo Marques Teixeira (2023)
The theme of this doctoral thesis is the actor training in the context of the technical demonstration Prisão para a Liberdade, by actor-researcher Carlos Simioni (LUME Teatro). What knowledge and practices operationalized in the technical demonstration of Prisão para a Liberdade can be considered fundamental for the updating Simioni's training? This was the guiding question of this research which assumes the close relationship between Simioni's training and Foucault's (1984) notion of self-care, aiming at identifying and problematizing the knowledge and the practices enabling the continued transformation of his training. The investigative journey was undertaken through bibliographic research, in works by Foucault (1974; 1983; 1984), Gumbrecht (2010), Icle (2010; 2011; 2013), Quilici (2015) and, mainly, through the critical-interpretative analysis of semi-structured interviews given to this researcher by Carlos Simioni, as well as the critical reflection on the technical demonstration Prisão para a Liberdade, resulting from the interpretative analysis of its audiovisual record. That way, the critical-reflexive immersion provided by the research allowed the understanding of Simioni's scenic manifestation as a living part of his existence, as a (not ordinary) way of expressing his singularities. The stage presence effect then becomes a possible consequence of his training.